Deconstructing Moral Responsibility in Oscar Wilde’s The Picture of Dorian Gray (1913) (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2026)
In determining the moral responsibility of an action, one may need to consider the possible conditions behind the action. Intuitively, an agent is morally responsible for an outcome only if an agent caused that outcome. However, there are possible conditions that can reject this perspective. Oscar Wilde’s The Picture of Dorian Gray (1913) provides an illustration regarding the complex evaluation of moral responsibility. This paper used a descriptive qualitative method to explore and provide a deeper description of this phenomenon. Ethics perspective reveals that Dorian is morally responsible for his actions by the existence of dominant binaries such as free will, involve, and harm. However, a deconstructive reading shows that there are marginalized binaries that are visible in the novel which contradict with the dominant binaries, namely influence, uninvolved, and conscience. This exposes the instabilities of hierarchical binaries of free will/influence, involve /uninvolved, harm/conscience. Aligning with Derrida's conception of différance, rather than opposed to the initial evaluation, the instabilities between the hierarchical binaries shows that the moral responsibility of Dorian Gray is complex, unstable, and continuously developing, suggesting that deconstructive reading provides an effective method for exposing the limitation of fixed meaning in assessing moral responsibility.